Simultaneous signaling in elimination contests - Jun Zhang (Queen's University, Department of Economics, 2008)
This paper analyzes the signaling effect of bidding in a two-round elimination contest. Before the final round, bids in the preliminary round are revealed and act as signals of the contestants' private valuations. Depending on his valuation, a contestant may have an incentive to bluff or sandbag in the preliminary round in order to gain an advantage in the final round. I analyze this signaling effect and characterize the equilibrium in this game. Compared to the benchmark model, in which private valuations are revealed automatically before the final round and thus no signaling of bids takes place, I find that strong contestants bluff and weak contestants sandbag. In a separating equilibrium, bids in the preliminary round fully reveal the contestants' private valuations. However, this signaling effect makes the equilibrium bidding strategy in the preliminary round steeper for high valuations and flatter for low valuations compared to the benchmark model.
Keywords: C72; D44; D82; 330; all-pay auction; elimination contests; incomplete; lottery; signaling; Auktionstheorie; Signalling; Unvollkommene Information; Spieltheorie